Congenital segmental dilatation of ascending colon with distal microcolon: A diagnostic dilemma - Ruchira Nandan; Vaibhav Pandey; Greeshma Suresh; Rajat Kumar Singh; Seth Kachhap (Wolters Kluwer Medknow Publications, 2023)
A 5-day-old male presented with bilious vomiting, a grossly distended abdomen, and passage of a small amount of stool. The anal opening was at a normal position. X-ray abdomen showed a large bowel loop with a single air-fluid level occupying more than half of the abdominal width. On laparotomy, the ascending colon was dilated to form a pouch-like structure, and the ileum and appendix were opening into it. Colon distal to pouch was present as microcolon. Histopathology of the dilated segment was suggestive of congenital segmental dilatation (CSD). In CSD, the distal bowel is of normal caliber. This is a rare case of CSD of ascending colon with distal microcolon.